2020
DOI: 10.1002/lno.11610
|View full text |Cite
|
Sign up to set email alerts
|

Massive silicon utilization facilitated by a benthic‐pelagic coupled feedback sustains deep‐sea sponge aggregations

Abstract: Biogeochemical cycling of silicon (Si), largely affected by biological drivers, is pivotal to the ecological functioning of the ocean. Most knowledge regarding biological utilization of Si derives from research on phototrophic organisms circumscribed to the photic ocean (i.e., diatoms). Utilization of Si in the aphotic ocean, where heterotrophic silicifiers become relevant Si users, remains poorly investigated. Here we quantify the flux rates and stocks characterizing Si cycling across dense aggregations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…Accumulations of dead individuals have been observed in the Sambro Bank Sponge Conservation Area (Hawkes et al, 2019), caused either by the displacement by high currents or by fishing activities and subsequent transport by the current (trawling and dumping). Our video data showed that large dead individuals were disintegrating in a period of several weeks, which might be important for the silicon cycling on the Scotian Shelf (Maldonado et al, 2020).…”
Section: Eventsmentioning
confidence: 76%
See 2 more Smart Citations
“…Accumulations of dead individuals have been observed in the Sambro Bank Sponge Conservation Area (Hawkes et al, 2019), caused either by the displacement by high currents or by fishing activities and subsequent transport by the current (trawling and dumping). Our video data showed that large dead individuals were disintegrating in a period of several weeks, which might be important for the silicon cycling on the Scotian Shelf (Maldonado et al, 2020).…”
Section: Eventsmentioning
confidence: 76%
“…This species is distributed along the continental margin of eastern North America, from the Florida Keys in the southern US, where it occurs in low densities, to the Scotian Shelf, where it forms extensive monospecific aggregations between ∼150 and 240 m depth in The Emerald Basin, reaching average densities of 3.8 ind. m −2 (Hawkes et al, 2019;Maldonado et al, 2020). Single individuals were found in an even broader depth range between ∼100 to 498 m depth on the Scotian Shelf (Beazley et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…These habitats are formed by three-dimensional structures created by the sponges, which provide refuge for other animals, sometimes of high economic value, and enhance biodiversity (e.g., Klitgaard, 1995;Beazley et al, 2013Beazley et al, , 2015Kenchington et al, 2013). Furthermore, because of their high pumping activity (Kutti et al, 2015) and consumption of organic matter (Leys et al, 2018), sponges play a major role in nutrient cycling (Maldonado et al, 2012), specifically in carbon turnover (Pile and Young, 2006;Yahel et al, 2007;Cathalot et al, 2015;Kahn et al, 2015), nitrogen flow (Hoffmann et al, 2009;Rooks et al, 2020) and the silicon cycle (Maldonado et al, 2020). Indeed, recently, studies point to serious impacts on ecosystem function when sponges are removed from the deep sea due to fishing bycatch (Pham et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In situ benthic measurements of net sponge fluxes include a) sampling the water inhaled and exhaled by the sponges in either deep-sea habitats using manned submersibles and ROVs (Pile and Young, 2006) or in shallow water using scuba diving (Morganti et al, 2017), or b) sampling through incubation chambers that may target either sponge individuals that are isolated from the external environment (Maldonado et al 2020a, Maldonado et al, 2020bLópez-Acosta et al, 2019) or small portions of the bottom and its benthic community (Roth et al, 2019;Yates and Halley, 2003).…”
Section: Methodological Approachmentioning
confidence: 99%